Research on the Development Path of Tourism in Hengqin Island - Yao, Mai; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
The construction of the Guangdong-Hong Kong-Macao Greater Bay Area relies on the basis of the joint development of the three places. It also reflects the new trend of diversified and integrated development. The goal of constructing a world-class tourism destination also becomes the guiding board of the Guangdong-Hong Kong-Macao Greater Bay Area’s construction. In this regard, Hengqin not only bears the responsibility of constructing a typical city that is suitable for living, working and sightseeing, but also owns a demonstrative significance for constructing a vital city cluster with international competitiveness and high-quality development. In the meantime, Hengqin is one of the first batch of free trade areas in China, as well as China’s third international leisure tourism island and the national all-for-one tourism demonstrative area, undertaking the important mission of the interactive development of Macao’s tourism industry. This paper will adopt the methods of investigation, literature research, quantitative analysis and qualitative analysis, and rely on two policies of "Hengqin-Guangdong-Macao Deep Cooperation Area" and "the Belt and Road" that jointly establish the tourism cooperation of the district and the country to study the development path of tourism in Hengqin.